FORMATION OF THE COMPONENTS OF ECOLOGICAL THINKING IN PRIMARY CLASS STUDENTS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The structure of sources of investment financing in Uzbekistan is changing in the following years. In particular, from year to year, the share of state budget funds is decreasing, and the share of funds from the enterprise, foreign direct investment and non-governmental funds is increasing. The article outlines the role of investment in the pursuit of economic progress and its effective use.